Effects of n−3 Polyunsaturated Fatty Acids on Cardiac Ion Channels - Moreno, Cristina; Macias, Alvaro; Prieto, Angela; de la Cruz, Alicia; Gonzalez, Teresa; Valenzuela, Carmen (Frontiers in Physiology, 2012)
Dietary n-3 polyunsaturated fatty acids (PUFAs) have been reported to exhibit antiarrhythmic properties, attributed to their capability to modulate ion channels. In the present review, we will focus on the effects of PUFAs on cardiac sodium channel (Nav1.5) and two potassium channels (Kv) (Kv1.5 and Kv11.1). n-3 marine (docohexaenoic and eicohexapentaenoic acid) and plant origin (alpha-linolenic acid) PUFAs block Kv1.5 and Kv11.1 channels at physiological concentrations. Also, DHA and EPA decreased Nav1.5 and calcium channels. These effects on Na and Ca channels theoretically should shorten the cardiac APD, whereas the blocking actions of n-3 PUFAs of Kv channels should lengthen the cardiac action potential. Experiments performed in female rabbits fed with a diet rich in n-3 PUFAs show a longer cardiac action potential and effective refractory period. This study was performed to analyze if their antiarrhythmic effects are due to a reduction of triangulation, reverse use-dependence, instability and dispersion of the cardiac action potential (TRIaD as a measure of proarrhythmic effects). Dietary n-3 PUFAs supplementation markedly reduced dofetilide-induced TRIaD and abolished dofetilide-induced torsades de pointes (TdP). Ultrafast sodium channel block by DHA may account for the antiarrhythmic protection of dietary supplements of n-3 PUFAs against dofetilide induced proarrhythmia observed in this animal model. The cardiac effects of n-3 PUFAs resemble those of amiodarone: both block sodium, calcium and potassium channels, have anti-adrenergic properties, can prolong the cardiac action potential, reverse TRIaD and suppress TdP. The main difference is that sodium channel block by n-3 PUFAs has a much faster onset and offset kinetics. Therefore, the electrophysiological profile of n-3 PUFAs appears more desirable: the duration of reduced sodium current (facilitates re-entry) is much shorter. The n-3 PUFAs appear as a safer alternative to other antiarrhythmic agents.